Energy expenditure of female international standard soccer players: A doubly labeled water investigation - Morehen, J. C.; Rosimus, C.; Cavanagh, B. P.; Hambly, C.; Speakman, J. R.; Elliott-Sale, K. J.; Hannon, M. P.; Morton, J. P. (Medicine & Science in Sports & Exercise, 2022)
Purpose The purpose of this study is to quantify total daily energy expenditure (TEE) of international adult female soccer players.